Simulação numérica do forjamento a quente de um aço baixo carbono em matriz fechada acoplado com a evolução microestrutural - Moraes, Araldo Luiz Isaias de (Universidade Federal de São Carlos, 2013)
Hot closed die forging is the most used process to produce metal parts used in supporting and fixing cable conductors in transmission lines of electric power. In this forming process, the microstructural quality of the products, in most cases, is dependent on the control of several parameters during processing such as the geometry of dies and the starting material, the number of stages of deformation, operational sequence, temperature, strain, strain rate, and others. Thus, this work aimed to analyze the process parameters such as temperature, strain and strain rate as well as the microstructural evolution during the hot closed die forging of a low carbon steel through the use of commercial software for analysis of forming processes based on finite element method. The numerical simulation of the complete process of hot forging of product ball hook was conducted, in order to reproduce the real industrial process. The results showed that the simulation was efficient to describe parameters evaluations, since the results obtained were consistent with those found in the real process and there was good agreement when comparing simulated average grain size and measured by optical microscopy.
Numerical simulation of hot closed die forging of a low carbon steel coupled with microstructure evolution
Keywords: Metalurgia; Simulação numérica; Parâmetros de processamento; Forjamento a quente; Evolução microestrutural; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA